Scope for resource mobilisation and expenditure control: A pragmatic approach - Vittal, N. (2004)
The basic problem in resource mobilisation and expenditure control is to find out a formula by which good economics is also good politics. Till now, inspite of not so healthy fiscal trends, political considerations have restrained some pragmatic and much needed reforms and restructuring measures. With the advent of coalition politics and the changing political paradigm, the strategy for resource mobilisation and expenditure control has to be free from parochial considerations and politically neutral. Besides the political will to rationalise expenditure policies, it is imperative that some novel approaches are adopted to locate areas of waste and implement innovative measures for controlling wasteful expenditure. - Reproduced.
Keywords: Resources management; Public expenditure